Pet detectives tortoise trouble - Hunter, Jana.; Blundell, Kim, illus (London : Collins, 2005)
Kara needs help to find her lost tortoise. This is just the case for a Pet Detective like me!
Purple Band 8.
Keywords: Detective -- Fiction; Pet detectives -- Fiction; Tortoise -- Fiction